Architectural materials for construction - Rosen, Harold J.; Heineman, Tom. (New York : McGraw-Hill, 1996)
This reference book features typical applications and specifications of all major architectural materials, from decorative concrete to exterior stainless steel. It covers information on sealants, membranes and coatings for moisture and thermal protection, as well as tiles, cermics and paints.
Part 1 Performance considerations. Part 2 Sitework: paving; retaining walls; garden walls; solar screens. Part 3 Architectural concrete: usages; ingredients; cast-in-place; precast; special techniques; architectural forms; protection; performance requirements. Part 4 Masonry: brick; concrete; masonry; structural glazed tiles; terra cotta; glass block; stone. Part 5 Metals: fabrication processes; aluminium; copper; stainless steel; steel. Part 6 Architectural woodwork: standards and requirements; glulam; veneers plywood and particle board; plastic laminate. Part 7 Thermal and moisture protection: built-up roofing; protected membrane roofing; single-ply sheet roofing; liquid-applied roofing membranes; waterproofing systems; sheet metal; thermal insulation; joint-sealing materials. Part 8 Glass and curtain walls: glass; glazing; surface protection of glass; metal curtain walls. Part 9 Finishes: flooring materials; cementitious materials; ceramic tile; resilient flooring; seamless flooring; terrazo; wood flooring; carpet; paints and coatings; painting.
Includes bibliographical references (pages 307-311) and index.
ARC
Department of Architecture
Keywords: Building materials; Architecture